Contrasting fish assemblages among floodplain ponds in a remnant riverine swamp - Hannah M. Holmquist; Adrian D. Macedo; Gregory W. Whitledge (Environmental Biology of Fishes, 2026)

Tracking pesticide accumulation in juvenile Chinook Salmon during outmigration through the Sacramento-San Joaquin River Delta - Hadis Miraly; S.D.M. Chinthaka; Kara E.Huff Hartz; Jacob Stagg; Shawn Acuña; Gregory Whitledge; Louise Cominassi; Amelie Segarra; Nann A. Fangue; Richard E. Connon; Michael J. Lydy (Environmental Pollution, 2026)

Development of a fipronil insecticide response spectrum model for juvenile Chinook salmon (Oncorhynchus tshawytscha) - Kara E. Huff Hartz; Katie J. Knaub; Louise Cominassi; Giovanni S. Molinari; Shane Power; Mia Arkles; S.D.M. Chinthaka; Andrea Chandler; Md. Habibullah-Al-Mamun; Gregory Whitledge; Amelie Segarra; Richard E. Connon; et al. (Environmental Pollution, 2025)

Using a critical body residue approach to assess the acute toxicity of a pesticide mixture to juvenile Chinook salmon (Oncorhynchus tshawytscha) - Kara E. Huff Hartz; Mia Arkles; Katie J. Knaub; Shane D. Power; Giovanni S. Molinari; S.D.M. Chinthaka; Gregory Whitledge; Amelie Segarra; Richard E. Connon; Shawn Acuña; Michael J. Lydy (Environmental Pollution, 2025)

Development of a response spectrum model for bifenthrin in juvenile Chinook Salmon (Oncorhynchus tshawytscha) - Katie Knaub; Md Habibullah-Al-Mamun; Kara E. Huff Hartz; Gregory Whitledge; Louise Cominassi; Andrea Chandler; Mia Arkles; John Reeve; Amelie Segarra; Richard E. Connon; Michael J. Lydy (Environmental Pollution, 2025)

Fish assemblage structure-habitat relationships in a riverine cypress swamp - Hannah M. Holmquist; Gregory W. Whitledge (Environmental Biology of Fishes, 2025)

The Roles of Diet and Habitat Use in Pesticide Bioaccumulation by Juvenile Chinook Salmon: Insights from Stable Isotopes and Fatty Acid Biomarkers - Sara E. Anzalone; Neil W. Fuller; Kara E. Huff Hartz; Gregory W. Whitledge; Jason T. Magnuson; Daniel Schlenk; Shawn Acuña; Matt R. Whiles; Michael J. Lydy (Archives of Environmental Contamination and Toxicology, 2024)

Habitat associations and demographics of a newly recorded population of taillight shiner in Illinois - Hannah M. Holmquist; Adrian D. Macedo; Brian A. Metzke; Gregory W. Whitledge (Environmental Biology of Fishes, 2024)

Comparison of resource use by invasive Black Carp and native fishes using isotopic niche analysis reveals spatial variation in potential competition - Hudman S. Evans; Alison A. Coulter; Ashley L. Johnson; James T. Lamer; Gregory W. Whitledge (Biological Invasions, 2023)

Effect of temperature and dietary pesticide exposure on neuroendocrine and olfactory responses in juvenile Chinook salmon (Oncorhynchus tshawytscha) - Jason T. Magnuson; Neil Fuller; Victoria McGruer; Kara E. Huff Hartz; Shawn Acuña; Gregory W. Whitledge; Michael J. Lydy; Daniel Schlenk (Environmental Pollution, 2023)

Establishment of invasive Black Carp (Mylopharyngodon piceus) in the Mississippi River basin: identifying sources and year classes contributing to recruitment - Gregory W. Whitledge; Patrick T. Kroboth; Duane C. Chapman; Quinton E. Phelps; Wes Sleeper; Jennifer Bailey; Jill A. Jenkins (Biological Invasions, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Recruitment contributions and natal fidelity in tributary rivers of the Grand Lake, Oklahoma, Paddlefish stock - Jason D. Schooley; Gregory W. Whitledge; Dennis L. Scarnecchia (Fisheries Management and Ecology, 2022)
Microchemistry of sectioned dentary (lower jaw) bones was used to determine natal river (Neosho, Spring or Elk River) of paddlefish Polyodon spathula (Walbaum) in the economically important snag fishery in Grand Lake, northeastern Oklahoma, and to assess the relative importance of the tributary rivers as sources of recruits to the fishery. Geological differences between the Neosho River and Spring River watersheds resulted in large differences in water strontium:calcium (Sr:Ca) ratios reflected in dentary Sr:Ca for paddlefish from each river. Dentary core Sr:Ca signatures were used to infer natal river for paddlefish harvested over the period 2008–2018. Most harvested fish (87%) were identified as Neosho River origin, and 7% were within the predicted range for Spring River origin (6% undetermined). Relative frequencies of Neosho River and Spring River‐origin fish (the latter, all ≤10%) differed among cohorts but did not differ among years, locations or sexes. Results corroborate a sonar survey of spawning substrates that concluded that the Neosho River has higher potential value for paddlefish spawning and recruitment than the Spring River. No evidence of natal river fidelity was found. Results highlight the importance of maintaining habitat conditions and inform harvest management regulations required for paddlefish spawning, recruitment and sustainability.

Listening with the invasive fish ear: applications and innovations of otolith chemistry analysis in invasive fish biology - Olivier Morissette; Gregory W. Whitledge (Environmental Biology of Fishes, 2022)

Environmental factors associated with silver carp presence and relative abundance near an invasion front to inform removal efforts - Michael A. Glubzinski; David P. Coulter; Gregory W. Whitledge (Hydrobiologia, 2021)

Effects of dietary cypermethrin exposure on swimming performance and expression of lipid homeostatic genes in livers of juvenile Chinook salmon, Oncorhynchus tshawytscha - Neil Fuller; Jason T. Magnuson; Kara E. Huff Hartz; Corie A. Fulton; Gregory W. Whitledge; Shawn Acuña; Daniel Schlenk; Michael J. Lydy (Ecotoxicology, 2021)

Identification of Bighead Carp and Silver Carp early-life environments and inferring Lock and Dam 19 passage in the Upper Mississippi River: insights from otolith chemistry - Gregory W. Whitledge; Brent Knights; Jon Vallazza; James Larson; Michael J. Weber; James T. Lamer; Quinton E. Phelps; Jacob D. Norman (Biological Invasions, 2019)

Multistate models of bigheaded carps in the Illinois River reveal spatial dynamics of invasive species - Alison A. Coulter; Marybeth K. Brey; Matthew Lubejko; Jahn L. Kallis; David P. Coulter; David C. Glover; Gregory W. Whitledge; James E. Garvey (Biological Invasions, 2018)

Recruitment sources and spatial patterns of population demographics of spotted bass in a large river–tributary network - Nicholas J. Abell; Devon C. Oliver; Gregory W. Whitledge (Fisheries Management and Ecology, 2018)
Understanding spatial patterns in population characteristics and the principal natal environments supporting riverine fish populations are important for fisheries management. Fin ray microchemistry was used to identify natal environment, and age estimates from sectioned fin rays were used to estimate growth and mortality rates for spotted bass, Micropterus punctulatus (Rafinesque), in a segment of the Ohio River (Smithland Pool) and three tributaries. Differences in water Sr:Ca and Ba:Ca among the Ohio River and tributaries were reflected in fin ray edge Sr:Ca and Ba:Ca. Fourteen percent of spotted bass ≥ age 2 captured in the Ohio River originated in tributaries, whereas 10% captured in tributaries originated in the Ohio River. Spotted bass in the Ohio River reached larger maximum size ( L∞ = 448.7) than conspecifics in tributaries ( L∞ = 324.4), although mortality rates were not different. Although 86% of spotted bass were collected in their inferred natal environment, small tributaries may be a supplemental source of recruitment for the spotted bass stock in Smithland Pool.

Fatty acid profiles are biomarkers of fish habitat use in a river-floodplain ecosystem - Neil P. Rude; Jesse T. Trushenski; Gregory W. Whitledge (Hydrobiologia, 2016)

Recruitment sources of invasive Bighead carp (Hypopthalmichthys nobilis) and Silver carp (H. molitrix) inhabiting the Illinois River - Jacob D. Norman; Gregory W. Whitledge (Biological Invasions, 2015)

Development and evaluation of species distribution models for fourteen native central U.S. fish species - Kristen L. Bouska; Gregory W. Whitledge; Christopher Lant (Hydrobiologia, 2015)

Habitat associations of fish assemblages in the Cache River, Illinois - Kristen L. Bouska; Gregory Whitledge (Environmental Biology of Fishes, 2014)

Otolith trace element and stable isotopic compositions differentiate fishes from the Middle Mississippi River, its tributaries, and floodplain lakes - John M. Zeigler; Gregory W. Whitledge (Hydrobiologia, 2011)

Assessment of otolith chemistry for identifying source environment of fishes in the lower Illinois River, Illinois - John M. Zeigler; Gregory W. Whitledge (Hydrobiologia, 2010)

Benthic community metabolism in three habitats in an Ozark stream - Gregory W. Whitledge; Charles F. Rabeni (Hydrobiologia, 2000)